Reduction of Asynchronous Motor Loss by Heuristic Methods (PSO-GA) - Dogan, M.; Dursun, M. (Elektronika ir Elektrotechnika, 2012)
The purpose of this article is to compensate the loss of performance caused by asynchronous motor feed. It was aimed to increase inverter output quality in order to reduce voltage instability at the current output and to minimize the harmonics of the inverters used to feed the motor. Many studies have made use of various algorithms to realize the aim mentioned in the article. Particle Swarm Optimization and Genetic Algorithm methods of optimization were used in this article to increase the current output quality, to minimize harmonics and to increase motor performance. Ill. 8, bibl. 15, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1053